2020
DOI: 10.7554/elife.55356
|View full text |Cite
|
Sign up to set email alerts
|

Shared and specific signatures of locomotor ataxia in mutant mice

Abstract: Several spontaneous mouse mutants with deficits in motor coordination and associated cerebellar neuropathology have been described. Intriguingly, both visible gait alterations and neuroanatomical abnormalities throughout the brain differ across mutants. We previously used the LocoMouse system to quantify specific deficits in locomotor coordination in mildly ataxic Purkinje cell degeneration mice (pcd; Machado et al., 2015). Here, we analyze the locomotor behavior of severely ataxic reeler mutants and compare a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 62 publications
0
21
3
1
Order By: Relevance
“…We first analyzed the locomotor behavior of GluA4-KO mice. Cerebellar dysfunction often leads to gait ataxia during walking, characterized by altered 3D limb trajectories and deficits in interlimb and whole-body coordination in both humans and mice ( Machado et al, 2020a ; Machado et al, 2015 ; Morton and Bastian, 2007 ). Surprisingly, we observed that GluA4-KO mice walked similarly to size-matched WT littermates without obvious gait ataxia ( Video 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We first analyzed the locomotor behavior of GluA4-KO mice. Cerebellar dysfunction often leads to gait ataxia during walking, characterized by altered 3D limb trajectories and deficits in interlimb and whole-body coordination in both humans and mice ( Machado et al, 2020a ; Machado et al, 2015 ; Morton and Bastian, 2007 ). Surprisingly, we observed that GluA4-KO mice walked similarly to size-matched WT littermates without obvious gait ataxia ( Video 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, we observed that GluA4-KO mice walked similarly to size-matched WT littermates without obvious gait ataxia ( Video 1 ). Quantitative analysis of locomotor coordination with the LocoMouse system ( Machado et al, 2020a ; Machado et al, 2015 ; Figure 7A–C ) revealed that their locomotor behavior was largely intact. GluA4-KO mice tended to walk more slowly than controls, but across walking speeds, stride lengths were comparable in mice of both genotypes ( Figure 7D–E , Figure 7—figure supplement 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cerebellum contains approximately 75% of all neurons in the brain ( Lange, 1975 ; Sarko et al, 2009 ) and integrates sensory inputs in order to fine-tune motor output ( Manto et al, 2012 ). This function is critical for motor coordination and motor learning as impairments in the cerebellar circuitry cause ataxia, dystonia, and tremor ( White et al, 2016 ; Bostan and Strick, 2018 ; Darmohray et al, 2019 ; Machado et al, 2020 ). The cerebellum also contributes to non-motor behaviors such as social interaction, reward, and memory ( Wagner et al, 2017 ; Carta et al, 2019 ; McAfee et al, 2019 ; Kelly et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cerebellum contains approximately 75% of all neurons in the brain (Lang et al, 1975; Sarko et al, 2009) and integrates sensory inputs in order to fine-tune motor output (Manto et al, 2012). This function is critical for motor coordination and motor learning as impairments in cerebellar circuity cause ataxia, dystonia, and tremor (White et al, 2016; Bostan and Strick, 2019; Darmohray et al, 2019; Machado et al, 2020). The cerebellum also contributes to non-motor behaviors such as social interaction, reward, and memory (Wagner et al, 2017; Carta et al, 2019; McAfee et al, 2019; Kelly et al, 2020).…”
Section: Introductionmentioning
confidence: 99%